Mechanistic study of photoinitiated free radical polymerization using thioxanthone thioacetic acid as one-component type II photoinitiator - Aydin, M; Arsu, N; Yagci, Y; Jockusch, S; Turro, NJ (AMER CHEMICAL SOC, 2005)
A mechanistic study concerning photoinitiated free radical polymerization using thioxanthone thio-acetic acid (TX-S-CH2-COOH) as one-component Type II photoinitiator was performed. Steady-state and time-resolved fluorescence and phosphorescence spectroscopy, as well as laser flash photolysis was employed to study the photophysics and photochemistry of TX-S-CH2-COOH. The initiator undergoes efficient intersystem crossing into the triplet state and the lowest triplet state posseses, pi- pi* configuration. In contrast to the unsubstituted thioxanthone, TX-S-CH2-COOH shows an unusually short triplet lifetime (65 ns) indicating an intramolecular reaction. From fluoroscence, phosphorescence, and laser flash photolysis studies, in conjunction with photopolymerization experiments, we propose that TX-S-CH2-COOH triplets undergo intramolecular electron transfer followed by hydrogen abstraction and decarboxylation producing alkyl radicals, which are the active initiator radicals in photoinduced polymerization. At low initiator concentrations (below 5 x 10(-3) M) this intramolecular reaction is the dominant path. At concentrations above 5 x 10(-3) M, however, the respective intermolecular reactions may be operative.
Keywords: LASER FLASH-PHOTOLYSIS; CARBOXYLIC-ACIDS; PHOTOSENSITIZED DECARBOXYLATION; PHOTOCHEMISTRY; DERIVATIVES; Polymer Science